Assessing the Relationship Between Inventory Accounting Information Systems and Operational Efficiency in Bandung's Manufacturing Firms - Dira Yogy Aprilla; Jimmy Rusjiana; Djadjun Djuhara; R. Deni Purana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This research addresses the main issue of how the Inventory Accounting Information System impacts the Internal Control of inventory in manufacturing companies in Bandung. The primary objective is to determine the influence of this accounting system on inventory control. The study employs a comprehensive descriptive and verificative method, focusing on manufacturing companies in Bandung. Data collection involves secondary data and hypothesis testing using linear regression analysis to provide a comprehensive understanding of the relationship between the Inventory Accounting Information System and Internal Control of inventory. The findings reveal a linear regression equation indicating a strong positive influence of the accounting system on internal control. Specifically, the Inventory Accounting Information System contributes significantly to the Internal Control of inventory in manufacturing companies, while the remaining influence is attributed to other unexamined variables. This research offers a novel insight into the critical role of effective inventory accounting systems in enhancing internal controls. The implications of these results highlight the necessity for manufacturing firms to optimize their inventory accounting practices to improve overall internal control.